Early Soybean Planting in a Water-Limited Growing Season - Sylvia R.G. Moraes; Bruno C. Pedreira; Vaishalai Sharda; Rodrigo B. Onofre; Gretchen F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2023)
Appropriate management, with a longer growing season during reproductive growth stages, can increase biomass and yield in soybean. Our objective was to determine the impact of three planting dates, two seed populations, and three maturity groups on grain yield in southeast Kansas. However, due to the severe drought in 2022, with a total rainfall of 18.84 inches during the soybean growing season (55% lower than the 10-yr average), the growing conditions were very limited, resulting in an average yield of 1.7 bu/a.
Keywords: field crop; planting date; biomass; charcoal rot